Press one for English : language policy, public opinion, and American identity - Schildkraut, Deborah J., 1973- (Princeton University Press, 2005)
"Press "One" for English examines how Americans form opinions on language policy issues such as declaring English the official language, printing documents in multiple languages, and bilingual education. Deborah Schildkraut shows that people's conceptions of American national identity play an integral role in shaping their views. Using insights from American political thought and intellectual history, she highlights several components of that identity and shows how they are brought to bear on debates about language. Her analysis expands the range of factors typically thought to explain attitudes in such policy areas, emphasizing in particular the role that civic republicanism's call for active and responsible citizenship plays in shaping opinion on language issues."